Relative Toxicity of Leaf Extracts of Eucalyptus globulus and Centella asiatica against Mosquito Vectors Aedes aegypti and Anopheles stephensi. (22nd October 2014) - Nair, Savitha Sekhar; Shetty, Vinaya; Shetty, Nadikere Jaya
Abstract : The larvicidal activity of different solvent leaf extracts (hexane, diethyl ether, dichloromethane, and methanol) of Eucalyptus globulus and Centella asiatica against two geographically different strains of Aedes aegypti and Anopheles stephensi was investigated. The extracts were tested against the late third instar larvae of Aedes aegypti and Anopheles stephensi, and larval mortality was observed after 24 hours of treatment. LC50 and LC90 were calculated. The LC50 values of hexane extract of Eucalyptus globulus against the late third instar larvae of the BSN and JPN strains of Aedes aegypti and the DLC and KNG strains of Anopheles stephensi were 225.2, 167.7, 118.8, and 192.8 ppm, while those of the hexane extract of Centella asiatica were 246.5, 268.7, 50.6, and 243.5 ppm, respectively. The LC50 values of diethyl ether extract of Centella asiatica were 339.6, 134.5, 241, and 14.7 ppm. The hexane extracts of both plants and the diethyl ether extract of C. asiatica presented the highest potential for the control of Aedes aegypti and Anopheles stephensi . The present findings also reveal the necessity of assaying multiple strains of a species to fully comprehend the larvicidal efficacy of a compound.